Pembuatan Nanozeolit dari Zeolit Alam Secara Top Down Menggunakan High Energy Milling dan Aplikasinya untuk Penyerapan Ion Fe 3+ - Agusetiani, Lilis (Chem Info Journal, 2013)
Has done research on facbrication nanozeolites from natural zeolite in top down use high energy milling and its application to adsorption Fe3+ Ions. The objective of this research is to fabrication nanozeolites from natural zeolite in top down using high-energy milling and determine levels of Fe3+ ions that can be adsorbed by the zeolite usual and zeolite nano. The method used in this research for the fabrication nanozeolites from natural zeolites in top down using high energy milling. Natural zeolites are sieved using a 225 mesh sieve and then milling with high energy milling with rotational speed of 1000 rpm for 6 hours. Natural zeolites product milling were activated by HF 1% and NH4Cl 2M. The results of research on natural zeolite pass 225 mesh sieve, natural zeolite after milling, and natural zeolite milling activation characterized using SEM and BET that indicates the size of surface morphology with specific surface of 125-250 nm, 75-100 nm, 50-75 nm and 33.997 cm3/g, 29.399 cm3/g, and 86.322 cm3/g, respectively. Concentration Fe3+ ions was analyzed using AAS with an optimum time of each 45 minutes, 15 minutes, and 150 minutes with the concentration of Fe3+ ions are adsorbed were164.98 ppm, 168.65 ppm, and 146.52 ppm